On Minimum-Dispersion Control of Nonlinear Diffusion Processes - Chertovskih, Roman; Pogodaev, Nikolay; Staritsyn, Maxim; A Pedro Aguiar (arXiv.org, 2024)
This work collects some methodological insights for numerical solution of a "minimum-dispersion" control problem for nonlinear stochastic differential equations, a particular relaxation of the covariance steering task. The main ingredient of our approach is the theoretical foundation called \(∞\)-order variational analysis. This framework consists in establishing an exact representation of the increment (\(∞\)-order variation) of the objective functional using the duality, implied by the transformation of the nonlinear stochastic control problem to a linear deterministic control of the Fokker-Planck equation. The resulting formula for the cost increment analytically represents a "law-feedback" control for the diffusion process. This control mechanism enables us to learn time-dependent coefficients for a predefined Markovian control structure using Monte Carlo simulations with a modest population of samples. Numerical experiments prove the vitality of our approach.